ПАССИВНЫЕ ДОМА В УКРАИНЕ И СТРАНАХ СНГ - Bozhko, I.K.; Lysenko, O.N.; Goncharuk, S.M.; Kalinina, M.F. (Institute of Engineering Thermophysics of NAS of Ukraine, 2018)
A brief overview and perspectives are provided and create passive houses in Ukraine and countries of UIC.